Impact of asymptomatic malaria infection on children’s growth in rural Malawi - Hany Sady; David Chaima; Lotta Hallamaa; Ulla Ashorn; Jomo Banda; Charles Mangani; John Kamwendo; Kenneth Maleta; Per Ashorn; Yue-Mei Fan (Scientific Reports)
Abstract Asymptomatic malaria infections are common in endemic regions, yet their impact on children’s growth remains inadequately understood. This study investigates the association between asymptomatic malaria and 6-18-month-old children’s growth indices in rural Malawi. Dried blood spots from 840 participants in Lungwena Child Nutrition Intervention 5 (LCNI-5) clinical trial were analysed at the baseline (N = 697) and every 3 months for a year. The associations between asymptomatic Plasmodium falciparum (determined by real-time PCR), and growth indices (length-for-age Z score (LAZ), weight-for-age Z score (WAZ), and weight-for-length Z score (WLZ)) were examined. Across all ages (6 to 18 months), malaria-positive children had lower mean WAZ (-1.03 vs. -0.87, 95% CI -0.17 − -0.04) and WLZ (-0.03 vs. -0.13, 95% CI -0.22 − -0.06) compared to those uninfected peers, whereas LAZ showed no significant association. However, no significant impact was observed at individual time points, except at 12 months of age. After adjusting for confounders, malaria infection remained associated with poorer children growth outcome. Asymptomatic malaria is linked to impaired growth outcomes among young children in rural Malawi. Targeted interventions aimed at managing asymptomatic malaria could mitigate growth faltering and improve child health in malaria-endemic settings.